Linking Structural Capabilities and Workplace Climate in Community Health Centers - Grant R. Martsolf PhD, MPH, RN; Scott Ashwood PhD; Mark W. Friedberg MD, MPP; Hector P. Rodriguez PhD, MPH (SAGE Publishing, 2018)
Many strategies to improve health care quality focus on improving the structural capabilities of primary care practices, including quality infrastructure and registry use, which are critical to managing chronic diseases. However, improving structural capabilities requires practices to expend significant resources and can be especially disruptive to community health centers (CHCs) serving high proportions of socioeconomically vulnerable patients. We explore the relationship between the structural capabilities and workplace climate in CHCs. The final sample for this analysis includes 25 CHC sites that could be matched across CHC site director surveys of structural capabilities and CHC adult primary care clinicians and staff (n = 446). To estimate the association between structural capabilities and dimensions of workplace climate, we estimated multivariate linear regression models that included the climate scales as dependent variables and the 5 structural capability scales as the main independent variables, with the 3 clinic-level and 2 staff-level covariates. More manageable clinic workload was associated with lower electronic record functionality (β = −0.47, P = .007), but positively associated with quality infrastructure (β = 0.92, P = .007). Staff relationships and quality improvement orientation were positively associated with quality infrastructure (β = 1.09, P = .006 and β = 0.87, P = .005). Manager readiness was associated with more robust quality infrastructure (β = 1.35, P = .016), but lower electronic record functionality (β = −0.48, P = .015) and less proactive patient outreach (β = −1.32, P = .025). Complex relationships between structural capabilities and workplace climate were found in CHCs. Further clarification of these complex connections may enable policy makers and practitioners to design and implement nuanced strategies to improve quality of care in CHCs.